Design and performance analysis of a twin T-bridge RC harmonic oscillation generator with an operational amplifier - Boyan Karapenev (IAES Indonesian Section, 2019)
This paper presents the special features of harmonic generators and their widespread use and in particular the design, simulation and experimental studies of a twin T-bridge RC generator with an operational amplifier. The results obtained are analyzed and compared. For the particular implementation, the frequency error varies from 4 % in experimental studies to 6.7 % in the simulation, and in this case an average value of 5.35 % can be assumed.